Aut Dedere As Erga Omnes To Suppress Civil Aviation Crimes Under The International Law: The Islamic Law Perspective - Mustapha Ismail Adua; Nik Salida Suhaila Nik Saleh (USIM PRESS, 2024)
Malaysian Journal of Syariah and Law (MJSL) Volume 12 Issue 1 Page (77-90)